Opportunities and challenges for machine learning in weather and climate modelling: hard, medium and soft AI - Chantry, M; Christensen, HM; Dueben, P; Palmer, T (Royal Society, 2021)
In September 2019, a workshop was held to highlight the growing area of applying machine learning techniques to improve weather and climate prediction. In this introductory piece, we outline the motivations, opportunities and challenges ahead in this exciting avenue of research. This article is part of the theme issue ‘Machine learning for weather and climate modelling’.